Effects of increasing standardized ileal digestible lysine:calorie ratio on gilts grown in a commercial finishing environment - Shelton, N.W.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 2,165 commercial gilts (PIC 337 × 1050) were used in two 4-wk studies to determine the lysine requirement for growing and finishing gilts. All diets were corn-soybean meal based and contained 0.15% L-lysine HCl and 3% added fat. Desired lysine levels were achieved by altering the corn and soybean meal level in the diet. Each experiment consisted of 6 treatments with 7 pens per treatment and 24 to 27 pigs per pen. In Exp. 1, 1,085 gilts (initially 84.2 lb) were used with standardized ileal digestible (SID) lysine:calorie ratios of 2.01, 2.30, 2.58, 2.87, 3.16, and 3.45 g/Mcal. Both ADG and F/G improved (quadratic, P < 0.003) with increasing SID lysine:calorie ratio, with the greatest improvement in performance through 3.16 g SID lysine/Mcal ME and a smaller increase to the highest SID lysine:calorie level. Daily SID lysine intake increased (linear, P < 0.001) and SID lysine intake per pound of gain increased (quadratic, P < 0.001) as expected with increasing dietary lysine. Income over feed costs (IOFC) and feed cost per pound of gain also followed a similar pattern (quadratic, P < 0.001). In Exp. 2, 1,080 gilts (initially 185.3 lb) were used with SID lysine:calorie ratios of 1.55, 1.75, 1.95, 2.05, 2.35, and 2.55 g/Mcal. As SID lysine:calorie ratio increased, ADG, F/G, daily SID lysine intake, SID lysine intake per pound of gain, IOFC, and feed cost per pound of gain improved (linear, P < 0.001) through the highest lysine:calorie level of 2.55 g/Mcal. These studies indicate that feeding higher levels of lysine than previously thought to be optimal offers significant economic and biologic improvements in growing and finishing gilts. More research is needed to validate the ideal SID lysine:calorie ratio for today’s evolving genetics.
Keywords: Gilt; Income over feed costs; Lysine